2014
DOI: 10.1177/0300985814559404
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Shedding and Barrier Function

Abstract: The intestinal epithelium is a critical component of the gut barrier. Composed of a single layer of intestinal epithelial cells (IECs) held together by tight junctions, this delicate structure prevents the transfer of harmful microorganisms, antigens, and toxins from the gut lumen into the circulation. The equilibrium between the rate of apoptosis and shedding of senescent epithelial cells at the villus tip, and the generation of new cells in the crypt, is key to maintaining tissue homeostasis. However, in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(144 citation statements)
references
References 84 publications
2
132
0
Order By: Relevance
“…As noted recently (Williams et al, 2015), remarkably little has been uncovered about homeo-static intestinal extrusion, including whether apoptosis precedes or follows extrusion. Nonetheless, most extruding human small intestine cells are caspase positive, and neighboring cells upregulate phosphorylated myosin light chain (Bullen et al, 2006), reminiscent of the multicellular actomyosin ring that accumulates around extruding apoptotic cells (Rosenblatt et al, 2001).…”
Section: A Force For Evil: Cell Extrusion In Diseasementioning
confidence: 99%
“…As noted recently (Williams et al, 2015), remarkably little has been uncovered about homeo-static intestinal extrusion, including whether apoptosis precedes or follows extrusion. Nonetheless, most extruding human small intestine cells are caspase positive, and neighboring cells upregulate phosphorylated myosin light chain (Bullen et al, 2006), reminiscent of the multicellular actomyosin ring that accumulates around extruding apoptotic cells (Rosenblatt et al, 2001).…”
Section: A Force For Evil: Cell Extrusion In Diseasementioning
confidence: 99%
“…Since the chloroform-methanol extracts that inhibited LPS activation of TLR4 demonstrated similar levels of competitive inhibition of LBP and CD14 binding and CL was a major component in those extracts, it was concluded that CL and perhaps other phospholipids were responsible for TLR4 inhibition. Studies in germfree mice revealed that the source of the CL was the host and most likely arose in the intestinal lumen by the turnover of intestinal epithelial cells (39,46). Indeed, studies have shown that intestinal commensal bacteria (19,39,46) and, specifically, LPS can regulate epithelial cell proliferation in a TLR4-dependent fashion in both health and disease (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…2C; Hopkins et al 2007; Chen et al 2014). In cells about to be extruded from the tip of the villus, ZO-1 and actin reorganize to form a “zipper” along the lateral membrane of live cells surrounding the apoptotic cell until the latter is completely extruded, and then the neighboring cells re-establish contact to reseal the epithelium (Guan et al 2011; Williams et al 2015; Madara 1990; Bullen et al 2006; Marchiando et al 2011). It is critical to maintain junctional integrity during cell migration and cell extrusion to prevent entry points to opportunistic pathogens that would disrupt homeostasis.…”
Section: Intestinal Epithelia Organization and Regulation Of Homeomentioning
confidence: 99%